درجة المنعة النفسية لدى الطلبة الموهوبين في الأردن - الصرايرة، خالد شاكر تركي (جامعة البحرين - مركز النشر العلمي, 2016)
The study aimed at recognizing the degree of psychological resilience of gifted students in Jordan. The study’s population consisted of 2800 students from 13 schools for the ‘gifted’ in the Hashemite Kingdom of Jordan. A sample of 307 gifted students was selected. The results of the study showed that the level of psychological resilience of the gifted students in Jordan was high. In addition, there were no significant differences found between genders in the level of psychological resilience amongst the gifted students in Jordan. Nevertheless, significant differences were found in the grade levels in the psychological resilience of gifted students in Jordan.
هدفت هذه الدراسة إلى تعرف مستوى المنعة النفسية لدى الطلبة الموهوبين في الأردن، وقد تكون مجتمع الدراسة من (2800) طالب وطالبه موزعين على (١٣) مدرسة حكومية لرعاية الموهوبين في المملكة الأردنية الهاشمية، واختيرت عينة متوافرة بلغ عددها (٣٠٧) من الطلبة الموهوبين في الأردن. وأظهرت النتائج أن مستوى المرونة لدى الطلبة الموهوبين في الأردن كان مرتفعا، بالإضافة إلى عدم وجود فروق في مستوى المنعة النفسية لدى الطلبة الموهوبين في الأردن يعزى لتغير الجنس، كما أشارت النتائج إلى وجود فروق في المنعة النفسية لدى الطلبة الموهوبين في الأردن تعزى لمتغير الصف الدراسي.
Keywords: الأردن -- الطلاب الموهوبون -- المنعة النفسية -- علم النفس التربوي